2022
DOI: 10.1021/acs.chemrestox.1c00254
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Isocitrate Dehydrogenase Mutations: Emerging Mechanisms for the Accumulation of the Oncometabolite 2-Hydroxyglutarate

Abstract: 2-Hydroxyglutarate (2-HG) is an unconventional oncometabolite of α-ketoglutarate. Isocitrate dehydrogenase mutation is generally acknowledged to be the main cause of 2-HG accumulation. In isocitrate dehydrogenase mutant tumors, 2-HG accumulation inhibits α-ketoglutarate/ Fe(II)-dependent dioxygenases, resulting in epigenetic alterations. Recently, the increase of 2-HG has also been observed in the cases of mitochondrial dysfunction and hypoxia. In these cases, 2-HG not only inhibits αketoglutarate/Fe(II)-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Previous reports have shown that inhibition of human 2OG oxygenases by both l - and d -2HG is possible 35 , 46 ; the concentration of d -2HG is elevated as a consequence of gain of function mutations to isocitrate dehydrogenases 1/2 (IDH 1/2) 47 , 48 . Mutations to the dehydrogenases converting l -2HG or d -2HG to 2OG can also result in elevations of l - or d -2HG levels 49 . Future work to systematically investigate the stereoselectivity of 2OG oxygenase inhibition by the 2HG enantiomers is therefore of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that inhibition of human 2OG oxygenases by both l - and d -2HG is possible 35 , 46 ; the concentration of d -2HG is elevated as a consequence of gain of function mutations to isocitrate dehydrogenases 1/2 (IDH 1/2) 47 , 48 . Mutations to the dehydrogenases converting l -2HG or d -2HG to 2OG can also result in elevations of l - or d -2HG levels 49 . Future work to systematically investigate the stereoselectivity of 2OG oxygenase inhibition by the 2HG enantiomers is therefore of interest.…”
Section: Resultsmentioning
confidence: 99%
“…This points to the existence of additional factors that contribute to the increased levels of 2-HG. In fact, several mechanisms independent of mIDH, leading to an increase in both D-2-HG and L-2-HG in tumors, have been reported [ 49 ].…”
Section: -Hg Metabolism In Physiological and Tumor Contextsmentioning
confidence: 99%
“…Concurrently, a distinguishing characteristic of tumor metabolism is the increased uptake of glutamine, coupled with intensified glutaminolysis within the mitochondria, mediated by glutaminase 1 (GLS1) [ 51 ]. This metabolic shift leads to a heightened accumulation of glutamine-derived α-KG, which can subsequently serve as the substrate for the synthesis of both D-2-HG and L-2-HG [ 49 , 52 ]. In RCC, a noted reduction in L2HGDH expression correlates with the consequential accumulation of L-2-HG [ 53 ].…”
Section: -Hg Metabolism In Physiological and Tumor Contextsmentioning
confidence: 99%